Water pollution status assessment of King Talal Dam, Jordan - Fandi, Khalid G.; Qudsieh, Isam Y.; Muyibi, Suleyman Aremu; Massadeh, Muhannad (AENSI Publications, 2009)
King Talal Dam (KTD) reservoir, Jordan's largest surface reservoir, is threatened by the activities of the catchment’s area, both domes tic and industrial, which emit untreated was te into the reservoir’s tributaries , consequently, raising the pollution and co n t aminating the water chemically and biologically. Therefore , the objective of this study was to assess the water quality and the pollution load to the reservoir in terms of some cardinal water quality parameters. Water samples obtained from inside and release outlet site of the dam were chemically tested by a n analyzing the presence of heavy metals, phenolic compounds, trace elements using as a screening tool ICP-MS, GCMS, and other equipment for phys ico-chemical and other parameters. For the biological screening, eosine methylene blue (EMB) media was used to investigate the presence of the fecal coliform and E. coli. Results obtained from this study showed that the concentration of analyzed metals (Cu, Zn, Cd, Cr, Fe, Hg, Pb, Mo and Mn) and other parameters (pH, EC, TDS, BOD, turbidity) are within the recommended standard limits for these contents in irrigation water. Also, results obtained from this study indicates the pollution tendencies of the surface waters of KTD reservoir, attributable to high levels of organic compounds .. Results revealed significant toxicity of phenolic compounds was found in water samples, indicating the water quality of these sample s is not potable. It is mainly due to the present of biological contamination. The maximum concentrations of phenol was (2.09 mg l-1) and (1.82 mg l-1) for outlet and inside water samples respectively. Among the selected phenolic compounds , the mos t frequently detected we re cyclohexane and benzene, which was found to be present in all sampling sites. All the analyzed samples of fecal coliform showed contaminated status ranging between 1.1 ´ 103 to 2.1 ´ 106 CFU 100 ml-1 from water and sewage samples respectively. E. coli counts were more than 1.1 ´ 102 CFU in 100 ml-1 in all samples which indicates that our irrigation water have biological pollution which is very alarming. This study provides a very useful amount of information for detecting potential toxicity risks .